Kompetensi Front Office dalam Meningkatkan Pelayanan di Kantor Pelayanan Pajak (KPP) Madya Surabaya - Nila Rosawatiningsih (Universitas Sultan Ageng Tirtayasa, 2019)
Bureaucratic problems especially in the public services is a big problem that is difficult to resolve. This is also experienced by Indonesia, but various efforts to improve public services have been carried out by focusing on the competence of Human Resources. Activities related to the development of the competency of the State Civil Apparatus (ASN) are clearly regulated in the legislation, however, the development of competencies for the front office in public institutions that are indeed serving as service directors and occupying the front work area has not been clearly regulated. This article highlights the phenomenon that occurred in the Tax Office (KPP) of Surabaya as a mid-level tax office in Surabaya. The existence of high demands from taxpayers in terms of excellent service makes a front office must be qualified. Front office as the front guard has a big responsibility because it reflects the good image of an institution. The purpose of this study is to find out what competencies are owned by the front office of the Surabaya KPP Madya in providing services. In order to achieve the intended goals, researchers use qualitative methods and conduct analysis using the Competency Theory. From the research conducted, researchers obtained results that front office competency was good enough.